Lucky day [videorecording (DVD)] - Avary, Roger; Bracey, Luke, 1989-; Dobrev, Nina, 1989-; Glover, Crispin (Lionsgate, 2019)
Red is a safe cracker who has just been freed from prison. He is trying to hold his family together as his past catches up with him. That past comes in the form of Luc, a psychopathic assassin who's seeking revenge for the death of his brother.